ANALISIS STRATEGI PENINGKATAN KINERJA RUMAH SAKIT MELALUI FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERILAKU PELAYANAN PADA RUMAH SAKIT LASINRANG KABUPATEN PINRANG - Arfiany Arfiany (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
Services becomes important for hospitals in Indonesia. This study analyzes the factors that influence the behavior of the service and its impact on organizational performance in RS Lasinrang Pinrang. The formulation of the problem is how to improve the behavior of the service. This study develops a research model and the four hypotheses to answer the problems that exist. Respondents in this study as many as 100 people. The respondents are the employees in RS Lasinrang. This study using Structural Equation Modeling (SEM) which run through AMOS 4:01 as a tool of analysis. The results showed that the research model and the results are acceptable. The research proves that the leadership, communication, and control systems have positive and significant influence on the behavior of the service. Furthermore, the behavior of services and significant positive effect on organizational performance. The higher the leadership, communication, and control systems, the higher the performance of the organization through service behavior. Based on these results, the theoretical implications that can provide a stronger justification for the antecedents that influence the behavior of services, such as leadership, communication, and control systems. Managerial implications of this research is the hospital management should give more attention to the evaluation and feedback activities, hospital management should increase the frequency of discussions with employees, and leaders need to set an example and encouragement to its employees.